Exploring the transmission mechanism of speculative and inventory arbitrage activity to commodity price volatility. Novel evidence for the US economy - Wei, Yao; Alexiou, Constantinos (Elsevier, 2022)
In the realm of monetary policy, we explore the transmission mechanism that relates speculative activity, inventory arbitrage activity, and commodity price volatility. In this direction, an ARMA-GARCH model is adopted to test this transmission effect on seven commodities using weekly U.S. data for the period 2008:12 to 2018:6. The results suggest that inventory arbitrage activities transmit monetary policy's effect onto commodities by strengthening the effect of the real interest rate on commodities' prices; in the case of palladium and crude oil's price conditional variances however the opposite effect is established. Speculative activities transmit monetary policy's effect mainly on commodities by increasing the positive effect of the real interest rate on metals and crude oil's prices, and on palladium and crude oil's price conditional variances. Our results show that inventory arbitrage activities are negatively related with commodities' prices, whilst speculative activities are positively related with commodities' prices. The two activities appear to exert mixed effects on commodities' price conditional volatilities. Additional evidence indicates that the relationship between the real interest rate and commodities' prices is positive and significant when unconventional monetary policy is considered, whilst we find that the real interest rate does not have any significant impact on most commodities' price conditional volatilities.
Keywords: Monetary policy; Commodity price volatility; Speculative activity; Inventory arbitrage activity; Transmission mechanism